SUBTITUSI JANTUNG PISANG DALAM PEMBUATAN ABON DARI PINDANG IKAN TONGKOL - Hardoko, Hardoko; Sari, Putri Yurida; Puspitasari, Yunita Eka (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
Boiled fish has various disadvantages such as short shelf life, less attractive appearance, consumers are limited, so we need a better product diversification. Research aimed to diversify into shredded boiled fish through substitution experiments of banana male bud 0%, 10%, 20%, 30%, 40%, and 50% (w/w) of the boiled meat mackerel fish. The results showed that the increased substitution of banana male bud tends to reduce levels of protein and moisture content, and tends to increase the fat content. Substitution of male banana bud against boiled fish up to 50% (w/w) produce shredded with characteristics of hedonic, fat content, ash content, and TBA are not-different from the substitution of 0%, but it has a higher yield, more fibrous texture, color brown more bright, water and protein levels the lower. The shredded of boiled fish banana male bud has a 54.26% yield, 5.97% moisture content, 25.86% fat, 33.04% protein, and lightness 34.83 (scale 0-100), so it is still included in the SNI shredded fish.